Institucionalização do Conhecimento em Sustentabilidade Ambiental pelos Programas de Pós-gradução Stricto Sensu em Administração - Celso Machado Junior; Maria Tereza Saraiva de Souza; Iara Regina dos Santos Parisotto (RAC: Revista de Administração Contemporânea, 2014)
This study analyzed the process of institutionalization and legitimization of knowledge in research-oriented (stricto sensu) management programs in the field of environmental sustainability by proposing and applying a theoretical model based on Berger and Luckmann. Berger and Luckmann’s sociology of knowledge, a theoretical interpretation of phenomena that develop in society, is used as the basis for the construction of a research model for institutionalization and legitimization processes. The research presents different methodological approaches that are inherently complementary, with a predominance of quantitative techniques, characterizing social network analysis as a mixed-methods approach. The research shows that collaborative networks formed by stricto sensu management programs contribute to the institutionalization and legitimization of knowledge in environmental sustainability. Bibliometrics and data mining techniques identified which authors have published works that are institutionalized and legitimized. The results show that the model developed by Berger and Luckmann allows the identification of authors and institutions that have institutionalized or legitimized the production of knowledge in environmental sustainability, something that can be applied in other scientific fields.